2011
DOI: 10.1007/s12265-011-9269-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ABCB1 Genotype on Pre- and Post-Cardiac Transplantation Plasma Lipid Concentrations

Abstract: Genetic variation of ATP-binding cassette subfamily B member 1 (ABCB1) which encodes P-glycoprotein (P-gp) has been associated with lipid levels and response to statins. Here, we studied these associations in patients with advanced heart failure who subsequently underwent transplantation. Fasting total cholesterol (TC), low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol and triglycerides (TG) concentrations in 268 adult heart transplant recipients were analysed retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…9 Variations in the ABCB1 gene encoding P-glycoprotein (P-gp) are associated with lipid levels and response to statins. 1 In cardiac transplant patients, the use of a triple immunosuppressive therapy ranges between 60-80%, and hyperlipidemia is an important cardiovascular risk factor in these patients. 1 In order to assess this relationship in patients with advanced heart failure, Taegtmeyer et al 1 confronted results of the genetic variation of ABCB1 with plasma LDL-c levels in patients before and after cardiac transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Variations in the ABCB1 gene encoding P-glycoprotein (P-gp) are associated with lipid levels and response to statins. 1 In cardiac transplant patients, the use of a triple immunosuppressive therapy ranges between 60-80%, and hyperlipidemia is an important cardiovascular risk factor in these patients. 1 In order to assess this relationship in patients with advanced heart failure, Taegtmeyer et al 1 confronted results of the genetic variation of ABCB1 with plasma LDL-c levels in patients before and after cardiac transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…1 In cardiac transplant patients, the use of a triple immunosuppressive therapy ranges between 60-80%, and hyperlipidemia is an important cardiovascular risk factor in these patients. 1 In order to assess this relationship in patients with advanced heart failure, Taegtmeyer et al 1 confronted results of the genetic variation of ABCB1 with plasma LDL-c levels in patients before and after cardiac transplantation. The authors observed an association between ABCB1 haplotype and plasma levels of LDL-c prior to transplanta-resuMo Polimorfismos de nucleotídeo único: uma perspectiva de prevenção cardiovascular Introdução: muitos estudos tem avaliado a utilização de biomarcadores lipídicos na tentativa de correlacioná-los com eventos clínicos cardiovasculares.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are summarized as: (i) Expression can be regulated by cholesterol levels, (ii) It is localized on cholesterol-rich cell membrane, (iii) It has a role in the reformation of proteoliposomes, and (iv) has high basal activity in the absence of cholesterol [21 -24]. Taegtmeyer et al studied MDR1 polymorphisms in adult heart transplant patients with advanced heart failure, and they found that there is an association between the ABCB1 haplotype and the fasting plasma LDL cholesterol concentration [25]. Fiegenbaum et al examined the relationship between lipid levels and C3435T/C1236T polymorphisms on hypercholesterolemic patients treated with simvastatin, and they reported that there is a significant decrease in the levels of total cholesterol and LDL cholesterol of individuals carrying non-homozygous 1236T variant allele [12].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type genotypes of 3435C<T and 2677G<T/A were also correlated to higher risk of graft rejection in a large cohort of 170 adult recipients [107], although in smaller cohorts these effects were not reproduced [94,100]. Other outcomes studied with these SNPs were new-onset diabetes [95] and plasma lipid concentrations [108]. Of these outcomes only higher LDL cholesterol pretransplant values were related to variant alleles of ABCB1, but this association was lost after transplantation.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%